STRATEGI PEMASARAN DALAM MENINGKATKAN NASABAH PADA ASURANSI SYARIAH PT ASURANSI JIWA SYARIAH BUMIPUTERA CABANG SURABAYA - Lilik Rahmawati; Farichatus Sholikhah; Hanifah Muslimah; Indi Rafiqa Amalia; Laila Maghfiroh (JURNAL PROFIT, 2021)
Sharia Insurance is an institution that provides services in the service sector that appears among people who still do not understand about sharia insurance and its mechanisms, so that people are still awkward to use the insurance services. Islamic insurance in Indonesia has the potential to grow along with the growth of the Islamic financial market. The sharia insurance strategy to increase product sales is carried out by conducting outreach to the public. In terms of increasing the number of customers, especially by expanding the market, especially for people who have not used sharia insurance services through direct socialization, maintaining and improving existing markets by trying to always maintain communication with customers to provide quality services, introducing financial planning and management. risk in Islamic insurance. Fast service provides convenience for more strategic management of needs so that it creates public interest in using sharia insurance services.